Modelled estimates of dissolved inorganic nitrogen exported to the Great Barrier Reef lagoon. (October 2021) - McCloskey, G.L.; Baheerathan, R.; Dougall, C.; Ellis, R.; Bennett, F.R.; Waters, D.; Darr, S.; Fentie, B.; Hateley, L.R.; Askildsen, M.
Abstract: Measuring stream pollutant loads across the Great Barrier Reef (GBR) catchment area (GBRCA) is challenging due to the spatial extent, climate variability, changing land use and evolving land management practices, and cost. Thus, models are used to estimate baseline pollutant loads. The eWater Source modelling framework is coupled with agricultural paddock scale models and the GBR Dynamic SedNet plugin to simulate dissolved inorganic nitrogen (DIN) generation and transport processes across the GBRCA. Catchment scale monitoring of flow and loads are used to calibrate the models, and performance is assessed qualitatively and quantitatively. Modelling indicates almost half (47%) of the total modelled DIN load exported to the GBR lagoon is from the Wet Tropics, and almost half of the total modelled DIN load is from sugarcane areas. We demonstrate that using locally developed, customised models coupled with a complementary monitoring program can produce reliable estimates of pollutant loads. Highlights: The eWater Source modelling framework was coupled to agricultural systems models. DIN processes are modelled at a daily time-step, at a subcatchment-land use-scale. Monitored and past modelled data are used to calibrate and evaluate modelled loads. 42% of the total modelled DIN exported is attributed to sugarcane cropping areas. Almost half of the modelled DIN load exported to the GBR is from the Wet Tropics.